Insights into the sand fly saliva: Blood-feeding and immune interactions between sand flies, hosts, and Leishmania. - Tereza Lestinova; Iva Rohousova; Michal Sima; Camila I de Oliveira; Petr Volf (Public Library of Science (PLoS), 2017)
Leishmaniases are parasitic diseases present worldwide that are transmitted to the vertebrate host by the bite of an infected sand fly during a blood feeding. Phlebotomine sand flies inoculate into the mammalian host Leishmania parasites embedded in promastigote secretory gel (PSG) with saliva, which is composed of a diverse group of molecules with pharmacological and immunomodulatory properties.In this review, we focus on 3 main aspects of sand fly salivary molecules: (1) structure and composition of salivary glands, including the properties of salivary molecules related to hemostasis and blood feeding, (2) immunomodulatory properties of salivary molecules and the diverse impacts of these molecules on leishmaniasis, ranging from disease exacerbation to vaccine development, and (3) use of salivary molecules for field applications, including monitoring host exposure to sand flies and the risk of Leishmania transmission. Studies showed interesting differences between salivary proteins of Phlebotomus and Lutzomyia species, however, no data were ever published on salivary proteins of Sergentomyia species.In the last 15 years, numerous studies have characterized sand fly salivary proteins and, in parallel, have addressed the impact of such molecules on the biology of the host-sand fly-parasite interaction. The results obtained shall pave the way for the development of field-application tools that could contribute to the management of leishmaniasis in endemic areas.